Analisis Upaya Peningkatan Kemampuan Literasi Pembelajaran Materi Transformasi Energi melalui Model Problem Based Learning Berbantuan Kartu Energi Pada Siswa Kelas IV SDN Kalibanteng Kidul 01 Semarang (International Forum of Researchers and Lecturers, 2023)
The background of writing this research is the result of observations during PPL 1 PPG pre-service that students' literacy skills are still low, especially in students' critical reasoning skills and literacy independence. Alternative learning as a solution is the application of the Problem Based Learning learning model assisted by Energy Cards. The purpose of this study is to describe learning literacy design, analyze process and result improvements, and determine the impact of implementing the Energy Card-assisted Problem Based Learning model. Data collection is carried out by test, observation, and documentation techniques. This research is a qualitative approach by looking for various theoretical descriptions, findings and other research materials obtained from reference materials to be used as a basis for activities. This study resulted in the percentage of students' critical reasoning ability and literacy independence with an average score of 85.8% (very good). The average student learning outcomes on the posttest were higher than the pretest with an increase of 20. The conclusion of this study is the design of learning literacy using the Energy Card-assisted Problem Based Learning model, the application of the Energy Card-assisted Problem Based Learning model is effective in improving student learning literacy skills, this study has an impact on students, teachers and schools.